PENGUKURAN KINERJA PERUSAHAAN DENGAN BALANCED SCORECARD - Abdullah Zailani (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2009)
Balance scorecard has a competitive advantage thet building strategic management systems now different with traditional management. Implementation in PDAM Magelang expected increase the quality of services, including in non financial. Therefore, PDAM has to measure its performance not only the financial aspect, but also non financial to reach goal congruence. This research reviews the implementation Balance Scorecard in PDAM Magelang. The analysis method using evaluation in performance measurement at four perspectives-financial perspective, customer perspective, internal business perspective, and innovation and learning perspective. The result shows that financial performance in PDAM Magelang appropriate with financial perpective on BSC. The customer perpective can not meet 80%, hut only 74% suitabel with BSC perspecttve. In internal bussiness perspective suitabel as health standard, have no taste, no smell and no color. The innovution and learning perspective can see on employee satisfaction. But in maintaining, placing and developing employees PDAM Magelang still not sfficient with BSC perspective. PDAM Magelang must develop its employees like give them opportunity to get education and increase the grade. Finally, placing its employess congruence with there skill and education.